Bibliometric analysis of single-cell sequencing researches on immune cells and their application of DNA damage repair in cancer immunotherapy - Zhao, Yu; Xiao, Yuanxun; Hu, Zhengbo; Wang, Ji; Xu, Zhiguang; Mo, Yizhang; Qi, Guojun; Chen, Kebing; Wu, Wu; Ma, Weiying (Frontiers in Oncology, 2023)
In recent decades, single-cell sequencing technology has developed rapidly and used widely in various fields of life sciences, especially for the detection of immune cells. A bibliometric analysis of single-cell sequencing research work on immune cells published during the 2011-2021 period should provide new insight on the use of single-cell sequencing. We screened 1,460 publications on single-cell sequencing on immune cells according to the publication date, article type, language, and country. The United States published the first and largest number of articles, while China's research started relatively late, but ranked second in the number of publications. T cells were the most commonly studied immune cells by single-cell sequencing, followed by mononuclear macrophages. Cancer biology was the most common field of immune cell research by single-cell sequencing. Single-cell sequencing studies using γδ T cells were mainly in the fields of cancer biology and cell development, and focused over time from cell surface receptor to cell function. Through in-depth analysis of the articles on single-cell sequencing of T cells in the oncology field, our analysis found that immunotherapy and tumor microenvironment were the most popular research directions in recent years. The combination of DNA damage repair and immunotherapy seems to provide a new strategy for cancer therapy.